Association of Cognitive Abilities and Brain Lateralization among Primary School Children in Kuwait. (26th May 2016) - Al-Hashel, Jasem Y.; Ahmed, Samar Farouk; Al-Mutairi, Hanouf; Hassan, Shahd; Al-Awadhi, Nora; Al-Saraji, Mariam
Abstract : Background . Many studies have explored the cognitive variation between left- and right-handed individuals; however, the differences remain poorly understood. Aim of the Work . To assess the association between brain lateralization indicated by handedness and cognitive abilities. Material and Methods . A total of 217 students aged between 7 and 10 years of both genders were identified for the study. Males and females were equally distributed. All left-handed students were chosen. An equal group with right-handed students was randomly selected. Handedness was assessed using traditional writing hand approach as well as the WatHand Cabient Test and the Grooved Pegboard Test. Cognition was measured using Cambridge University's CANTAB eclipse cognitive battery. Pearson Correlation Coefficient Test "r " was calculated to measure the strength of association between quantitative data. Results . Right-handed children had superior visuospatial abilities (p = 0.011, r = 0.253 ), visual memory (p = 0.034, r = 0.205 ), and better scores in reaction time tests which incorporated elements of visual memory (p = 0.004, r = - 0.271 ). Left-handed children proved to have better simple reaction times (p = 0.036, r = 0.201 ). Conclusion . Right-handed children had superior visuospatial abilities and left-handed children have better simple reaction times.